Underlying event measurement in dilepton channel with CMS detector / Fahmi Maulida - Fahmi , Maulida (2018)
The measurements of the charged particles can shed alight on the non-perturbative QCD regimeat the LH Can don the universality of the behavior of the Underlying Event (UE) in proton-proton collisions. In this thesis, the proton-proton collision data acquired by the CMS experiment at a centre-of-massenergy of 13 Te V and corresponding to an integrated luminosity of35.9fb